PELATIHAN PEMBUATAN PROPOSAL PENGAJUAN BANTUAN MESIN PENGGILING PAKAN IKAN LELE DESA CODO KECAMATAN WAJAK - Retno Palupi; Yuswanti Dwi Cahyani (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2022)
The aim of this training is to train catfish farmers in Codo village to be able to prepare proposals for submitting assistance for catfish feed processing equipment. Students of the Real Work Lecture at the State University of Malang who are conducting the Real Work Lecture in Codo Village, Wajak District, Malang Regency, are holding an Entrepreneurship Training activity with the theme